Leading virtual teams : expert solutions to everyday challenges. (Pocket mentor series., 2010)
"How do you lead a team scattered across the globe? How do you keep members you can't see organized, communicative, and productive? In this book, you'll find valuable advice on forming virtual teams, assessing their communication and technology needs, and ensuring that they produce high-quality work. You'll learn how to: (1) Understand the benefits and challenges of virtual teams, (2) Build a virtual community that promotes collaboration and ongoing communication, (3) Utilize technology to enhance your virtual team's focus, motivation, and output. Meet Your Mentors: Jessica Lipnack and Jeffrey Stamps are CEO and Chief Scientist, respectively, of the Boston-based consulting firm NetAge and authors of many books and articles on networked organizations, including Virtual Teams."--Publisher's website.